Endogenous income distribution in the Bhaduri-Marglin model - Bernhard Schütz (Intervention. European Journal of Economics and Economic Policies, 2012)
The results of the Bhaduri-Marglin model build on the assumption of an exogenous profit share. The present paper examines critically the robustness of these results by asking how its results change if we take the endogeneity of the profit share into account. In doing so, the constituents of the latter (labor productivity and the real wage rate) are treated as endogenous. The paper finds that the conditions for wage- and profit-led regimes only change when we assume increases in the real wage rate to be followed by very strong labor rationalization. Furthermore, the paper shows how these additional channels can increase or decrease the profit-led/wage-led character of a regime and how they may even become a source of instability.
Keywords: E12; E21; E22; E25; 330; Income distribution; wage-led/profit-led demand regimes; labor ra-tionalization